The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00216-012-5776-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses related to agonistic, antagonistic and synergistic interactions of chemical species

Abstract: The fact that the essential or toxic character of elements is species specific has encouraged the development of analytical strategies for chemical speciation over the last twenty years; indeed, there are now a great number of them that provide very good performance. However, biological systems are exposed to a complex environment in which species of elements can interact in a synergistic/antagonistic fashion. Thus, the metabolism of trace elements cannot be considered in isolation. On the other hand, biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 258 publications
(205 reference statements)
1
35
0
Order By: Relevance
“…The protective effect of selenium on mercury toxicity has been issued in several papers [1][2][3][4][5][6] as well as the antagonist action of selenium against carcinogenic and/or neurotoxic chemicals. [7][8][9] Simultaneous injection of sodium selenite with mercury chloride (at different sites to avoid precipitation) completely protects rats from the characteristic histological changes associated with mercury chloride toxicity. 10 Further studies have demonstrated this protective effect of selenium in mice, 11 pigs, 12 chicken, 13 fishes 2 and rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of selenium on mercury toxicity has been issued in several papers [1][2][3][4][5][6] as well as the antagonist action of selenium against carcinogenic and/or neurotoxic chemicals. [7][8][9] Simultaneous injection of sodium selenite with mercury chloride (at different sites to avoid precipitation) completely protects rats from the characteristic histological changes associated with mercury chloride toxicity. 10 Further studies have demonstrated this protective effect of selenium in mice, 11 pigs, 12 chicken, 13 fishes 2 and rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between elements depend on the chemical species and organism type [85]. In rodents, Se prevents As-induced cytotoxicity when arsenite and selenite are simultaneously administered to mice and hamster [86][87][88].…”
Section: Metals Interactions Under Environmental Metal Stressmentioning
confidence: 99%
“…Hg-induced apoptosis [99], represents a defence against methylmercury (MeHg + ) toxicity [100] and causes Hg detoxification [101], between others. The study of species interactions of elements in biological organisms requires experts from various fields such as biology, chemistry, medicine, biochemistry, molecular biology and genetics [85]. In addition, in real environments, animals are exposed to multiple elements that interact among them, so that the assessment of biological response has to be oriented to the toxicological effects caused by the combination of metal/metalloids and their species.…”
Section: Metals Interactions Under Environmental Metal Stressmentioning
confidence: 99%
“…Data from such analysis are used to compute mobility and bioavailability of metals [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%